Associations between MHC class I variation and blood pathogen prevalence in caracal - Ly, Alicia (Percy FitzPatrick Institute of African Ornithology, 2017)
Adaptive genetic variability is vital to long-term species survival, as it presents the potential for evolutionary adaptive responses to environmental change. Genes of the Major Histocompatibility Complex (MHC) trigger the vertebrate adaptive immune response to pathogens through the recognition and presentation of foreign peptides, and thus provide an informative genetic marker for studying the adaptive potential of species with respect to disease. MHC class I loci mediate the immune system's recognition of intracellular pathogens, including protozoans, viruses and bacteria, and the high levels of genetic diversity reported at these loci is thought to be primarily the result of pathogen-mediated selection. Although variation within a number of MHC genes has been described in many felid species, the relationship between MHC diversity and pathogen prevalence within wild felid populations has rarely been examined previously. Because many wild felids are highly sensitive to the effects of anthropogenic-induced environmental changes, evolutionarily relevant adaptive genetic variation is particularly important for their conservation. This study explored the relationship between MHC class I exon 2 and exon 3 diversity and a number of tick-borne blood pathogens in a population of caracal (Caracal caracal) in the urban landscape of Cape Town, South Africa. The characterization of MHC class I diversity identified 38 and 45 unique, putatively functional alleles in the population, from exon 2 and exon 3 respectively. The influence of MHC allelic diversity and specific alleles, together with sex, age class, home range size and urban cover within home range, on individual pathogen prevalence was assessed using Generalized Linear Models. A positive relationship between Babesia infection and multiple measures of MHC diversity, including nucleotide diversity, average number of nucleotide differences and number of exon 3 alleles, was detected. Additionally, the presence of two specific alleles was significantly correlated with Babesia infection. High levels of infection by a number of tick-borne pathogens were observed in the population, suggesting environmental factors also have an important influence on pathogen prevalence. However, home range and urban cover within home range, as well as sex and age, were not significantly associated with Babesia infection. This study provides the first assessment of the relationship between MHC class I adaptive genetic variation and individual pathogen prevalence in caracal.